Disulfiram thermosensitive in-situ gel based on solid dispersion for cataract - Chunjuan Zhang; Tonghua Xu; Donglei Zhang; Wei He; Siling Wang; Tongying Jiang (Elsevier, 2018)
To improve the corneal permeability and water-solubility of disulfiram (DSF), which is an ocular drug for cataract, P188 was selected as a matrix to prepare solid dispersion of DSF (DSFSD) by hot melt method. The DSFSD was characterized by DSC, XRD, and IR, and the results suggested that DSF was amorphous in DSFSD. The DSFSD was added to borate buffer solution (BBS) contained 20% poloxamer P407 and 1.2% poloxamer P188 to form in-situ gel. In vitro and in vivo experiments revealed that DSFSD combined with in-situ gel (DSFSD/in-situ gel) increased the residence time and the amount of DSF penetrated through the corneal. The pharmacodynamics studies exhibited DSFSD/in-situ gel delayed the development of selenium-induced cataract at some content. These results investigated that DSFSD/in-situ gel as a drug delivery system can improve DSF ocular permeability. Keywords: Disulfiram, Solid dispersion, In-situ gel, Permeability, Anti-cataract